2001
DOI: 10.2134/jeq2001.3041382x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Leachates from Coal Refuse Blended with Fly Ash at Different Rates

Abstract: There is great interest in returning coal combustion products to mining sites for beneficial reuse as liming agents. A column study examined the effects of blending two coal fly ashes with an acid-forming coal refuse (4% pyritic S). Both fly ashes were net alkaline, but had relatively low neutralizing capacities. One ash with moderate alkalinity (CRF) was bulk blended with coal refuse at 0, 20, and 33% (w/w), while another lower alkalinity ash (WVF) was blended at 0, 5, 10, 20, and 33% (w/w). The columns were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…2), the overall results differed. First of all, coal refuse materials generally contain much more finely divided reactive sulfides than coal mine spoils and are much finer textured (Stewart et al 2001;Daniels et al 2009), and therefore produce much higher levels of both initial and long-term EC/TDS. These particular refuse materials are unusual for our region in that all contain a significant surplus of neutralizers over potential acidity (Table 1), and all three materials produced moderate (pH 5) to relatively high leachate pH ([7) over time as expected.…”
Section: Column Leaching Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2), the overall results differed. First of all, coal refuse materials generally contain much more finely divided reactive sulfides than coal mine spoils and are much finer textured (Stewart et al 2001;Daniels et al 2009), and therefore produce much higher levels of both initial and long-term EC/TDS. These particular refuse materials are unusual for our region in that all contain a significant surplus of neutralizers over potential acidity (Table 1), and all three materials produced moderate (pH 5) to relatively high leachate pH ([7) over time as expected.…”
Section: Column Leaching Resultsmentioning
confidence: 99%
“…For the past two decades, we have focused research efforts on the utilization of a laboratory column leaching procedure to characterize leaching potentials and risks from a wide range of coal mining related materials including coal refuse and fly ash (Stewart et al 2001;Daniels et al 2009) and coal mine spoils (Orndorff et al 2010;Daniels et al 2013Daniels et al , 2014. In this paper, we summarize our findings with respect to hard rock derived coal mine spoils with reference to coal refuse materials as well.…”
Section: Tds Prediction Researchmentioning
confidence: 99%
“…In the case of highly alkaline fly ash or non-acidic coal refuse, for example, the TCLP procedure tests these materials in a moderately acidic (glacial acetic acid) environment. This extraction environment may be drastically different from the conditions governing leachability under actual co-disposal conditions, and we have previously reported (Stewart et al, 2001) significant metal leaching from fly ash materials that easily "passed" the TCLP test. General chemical properties and total elemental concentrations of As, Se, Cr, and Mo obtained by total digestion of the five selected CCPs are presented in Table 2.…”
Section: Ccp Chemical Propertiesmentioning
confidence: 97%
“…Therefore, drainage from coal waste, which is initially alkaline, remains alkaline for a certain period of time and then tends to become acidic. This period can be extended by addition of alkaline materials which is a widely accepted mine reclamation practice (Dreher et al 1994;Nawrot and Gray 2000;Stewart et al 2001). Chugh et al (2007a, b) and others have suggested that differential AP and NP rates could be used advantageously in waste management operations to allow for improved placement and compaction practices, and reduction of SO 4 discharges.…”
Section: Research Hypothesis and Overall Researchmentioning
confidence: 99%